Uso da química forense como ferramenta de ensino através da aprendizagem significativa - Souza, Ana Kedyna Ribeiro de (2017)
The Chemistry teaching on the Higt School is usually characterized as a learning process, guided by memorization and meaninglessness. Teachers often show a few difficulties in relating the Chemistry itself with daily life events and they prioritize the traditional methodology. This work introduces a meaningful learning proposal by using the forensic Chemistry. The study was applied at a high school located at the city of Maracanaú, Fortaleza’s metropolitan region, aiming to contribute to the meaningful learning at the Chemistry’s discipline and analyze the student’s perceptions related to the interest and comprehension of Chemical phenomena. On the methodological course, the matter of violence on the city was addressed in dialogue with the forensic Chemistry, by elucidating, according to the chemical experimentation, fictions crimes, which were associated to the contents of Chemistry, as acids and bases, oxidation and reduction, solubility, intermolecular interaction, organic functions and many others. Three instruments were used to obtain data: firstly, a redaction for selecting the students; after this, a questionnaire that analyzed the previous knowledge; and then, a second questionnaire that checked the new learning appearance. The main results pointed divergences on the students behavior, by the development of skills and competences. It was concluded that the recovery of the students’ interest for Chemistry made a positive contribution to the meaningful learning of chemical formal contents.